(untitled) (Applied Biological Research, 2020)
The influence of three hydrocolloids namely xanthan gum, pectin, and guar gum at concentrations of 1.5% were studied to assess the cloud stability of sea buckthorn squash. The prepared squash was subjected to physicochemical, phenolic, antioxidant and sensory evaluation at 0, 30, 60 and 90 days of storage. In general, there was an increase in TSS, reducing and total sugars while decrease in acidity, ascorbic acid, carotenoids, phenolic compounds and antioxidant activity was observed in prepared sea buckthorn squash than pulp. During storage, sea buckthorn squash showed increase in acidity, TSS, reducing and total sugars in all the treatments. The squash containing pectin showed the high ascorbic acid content and squash containing guar gum showed high carotenoid contents at the end of storage period. The prepared squash treated with pectin and guar gumshowed slight decrease in antioxidant activity while as high loss of antioxidant activity was observed in xanthan gum treatment at the end of storage. A declining trend was also observed in phenolic compounds in all the treatments during storage. HPLC analysis revealed that three phenolic compounds were present in pulp which was significantly (p<0.05) reduced in all the treatments in squash during storage period. Sea buckthorn squash containing pectin showed higher color and taste values followed by guar gum and xanthan gum during storage.